Feathers, folklore, and eco-literacy: stories ascribe cultural keystone status to avian scavengers in South Asian cities - Gupta, U; Kumar, N (Oxford University Press, 2024)
We examined the cultural significance of commensal avian scavenger species—vultures, kites, and crows—and their exploitation of anthropogenic resources and sentiments within Delhi’s urban landscapes. For this, we investigated the intrinsic values attributed to these birds by people, which are indicative of complex, rapidly urbanizing social-ecological systems. Semi-structured interviews revealed folk perceptions intertwined with socio-cultural narratives and traditions, shaped by observations of avian morphology, ecology, and behavior. Birds’ nesting habits, habitats, home ranges, and foraging behaviors affected people’s perceptions, while ecosystem services inspired zoomorphism and anthropomorphism via vernacular-nomenclature (e.g., chidiya collectively for songbirds, giddha for scavenging raptors). Culturally rooted perceptions, which informed ritual feeding practices and shaped prevalent attitudes towards commensal species, fostered mutual tolerance, and brought people into closer contact with urban biodiversity. Such physical and cultural proximity is a defining characteristic distinguishing tropical urban ecosystems from their Western counterparts. We also uncovered the web of social-technological influences on animal-related folk stories. The urbanization of perceptions in vulture extinction zones revealed shifts in social-ecological relationships with wildlife. It adds cultural dimensions to the currently appreciated keystone status of vultures, vital for their erstwhile coexistence at extremely high densities in South Asia. Urban transformations, technological advancements, and media exposure potentially reshaped human–animal interface, with media misinformation affecting personalized ecologies. Conflicts and health concerns arose from media narratives on garbage-consuming animals. Our findings offer insights to prevent severing of people and nature connections due to urbanization (e.g., technological applications can integrate scientific knowledge with biocultural narratives and folklore), promoting a new-age eco-literacy.